Використання когнітивного моделювання в професії маркетолога - Параниця, Надія Володимирівна; Паянок, Тетяна Миколаївна; Савченко, Алла Миколаївна; Кравчук, Анна Олександрівна; Паянок, Тетяна (Видавнича група «Наукові перспективи», 2024)
Важливим аспектом дослідження стало вивчення технології когнітивного моделювання в рамках формування та розвитку професії маркетолога. Вивчено суть когнітивного моделювання, яка полягає у дослідженні причинно-наслідкових зв’язків, що визначають зовнішній вплив на можливі сценарії стратегічного розвитку маркетингової діяльності. У вигляді виваженого орграфа розроблено когнітивну карту умов планування та прогнозування в професії маркетолога з урахуванням коефіцієнта новизни із застосуванням комп’ютерної системи Pajek проведено імітаційне моделювання ймовірних ситуацій та проаналізовано альтернативні сценарії розвитку та зміни сили впливу сигналів зовнішнього середовища. Сучасні дослідження все активніше використовують когнітивний аналіз для вивчення функціонування великих систем в умовах невизначеності. Цей підхід дозволяє ефективно управляти розвитком подій у таких системах. Використовуючи когнітивну структуру для організації знань експертів, науковці змогли створити формалізовану модель українських регіонів. Ця модель, реалізована в сучасному середовищі когнітивного моделювання, забезпечує науково обґрунтовані результати щодо динаміки ключових показників, які відображають тенденції розвитку регіонів. У статті обґрунтовано необхідність використання когнітивного моделювання для розробки концептуальних основ професії маркетолога. Описано основні етапи та роз’яснено методику когнітивного моделювання для створення сценаріїв розвитку окремих регіонів України. Автором розділено групи взаємопов’язаних факторів та умов, що впливають на розвиток регіонів, визначивши їх як ключові характеристики для забезпечення конкурентоспроможності та еволюції. На основі когнітивного моделювання у статті запропоновано й обґрунтовано стратегії маркетингового дослідження. Сьогодні ефективне управління інформаційними потоками є важливим чинником успіху будь-якої організації. Когнітивні обчислення, як нова галузь штучного інтелекту, пропонують інноваційні рішення для обробки великих обсягів як структурованих, так і неструктурованих даних. Ці технології дозволяють автоматизувати рутинні процеси, виявляти закономірності та ефективно приймати обґрунтовані рішення на основі аналізу інформації.

An important aspect of the research was the study of cognitive modeling technology within the framework of the formation and development of the marketing profession. The essence of cognitive modeling is studied, which consists in the study of cause-and-effect relationships that determine the external influence on possible scenarios of strategic development of marketing activities. A cognitive map of the conditions of planning and forecasting in the marketing profession was developed in the form of a balanced orthograph, taking into account the novelty factor, using the Pajek computer system, simulation modeling of probable situations was carried out, and alternative scenarios of development and changes in the influence of environmental signals were analyzed. Modern research is increasingly using cognitive analysis to study the functioning of large systems under conditions of uncertainty. This approach allows you to effectively manage the development of events in such systems. Using a cognitive structure to organize experts’ knowledge, scientists were able to create a formalized model of Ukrainian regions. This model, implemented in a modern cognitive modeling environment, provides scientifically based results regarding the dynamics of key indicators that reflect the development trends of the regions. The article substantiates the necessity of using cognitive modeling to develop the conceptual foundations of the marketing profession. The main stages are described and the methodology of cognitive modeling for creating development scenarios of individual regions of Ukraine is explained. The author divided the groups of interrelated factors and conditions affecting the development of regions, identifying them as key characteristics for ensuring competitiveness and evolution. On the basis of cognitive modeling, the article proposes and substantiates marketing research strategies. Today, effective management of information flows is an important factor in the success of any organization. Cognitive computing, as a new branch of artificial intelligence, offers innovative solutions for processing large volumes of both structured and unstructured data. These technologies make it possible to automate routine processes, identify patterns and effectively make informed decisions based on information analysis. In today’s conditions of dynamic development of market relations and increased competition, it is becoming more and more difficult for marketers to predict consumer behavior, analyze large volumes of data, and develop effective strategies for promoting goods and services. Traditional methods of marketing analysis in many cases are not flexible enough and do not allow taking into account all factors affecting market processes. One of the innovative approaches that can significantly improve the quality of decision-making in marketing activities is cognitive modeling. However, the issue of effective use of this method in the marketing profession remains insufficiently researched and requires additional attention.
Keywords: маркетинг; когнітивне моделювання; поведінкові патерни; маркетинговий інструментарій; споживачі; marketing; cognitive modeling; behavioral patterns; marketing tools; consumers